Recognition and kinetics for excision of a base lesion within clustered DNA damage by the Escherichia coli proteins Fpg and Nth. - David-Cordonnier, M; Laval, J; O'Neill, P (2001)
Ionizing radiation and radiomimetic anticancer agents induce clustered DNA damages that are thought to lead to deleterious biological consequences, due to the challenge that clustered damage may present to the repair machinery of the cell. Specific oligonucleotides, containing either dihydrothymine (DHT) or 7,8-dihydro-8-oxoguanine (8-oxoG) opposite to specific lesions at defined positions on the complementary strand, have been used to determine the kinetic constants, K(M), k(cat), and specificity constants, for excision of DHT and 8-oxoG by the Escherichia coli base excision repair proteins, endonuclease III (Nth) and formamidopyrimidine glycosylase (Fpg), respectively. For excision of DHT opposite to 8-oxoadenine by Nth or Fpg proteins, or 8-oxoG opposite to 8-oxoG by Fpg, the major change in the specificity constant occurs when the second lesion on the complementary strand is one base to the site opposite to DHT or 8-oxoG. The specificity constants for excision of DHT or 8-oxoG by both proteins are reduced by up to 2 orders of magnitude when an abasic site or a strand break is opposite on the complementary strand. Whereas the values of K(M) are only slightly affected by the presence of a second lesion, the major change is seen as a reduction in the values of k(cat). The binding of Fpg protein to oligonucleotides containing 8-oxoG is inhibited, particularly when a single strand break is near to 8-oxoG on the complementary strand. It is inferred that not only the binding affinity of Fpg protein to the base lesion but also the rate of excision of the damaged base is reduced by the presence of another lesion, particularly a single strand break or an AP site on the complementary strand.